2002
DOI: 10.1034/j.1600-6143.2002.20507.x
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Does Not Exhibit Nephrotoxicity Compared to Cyclosporine in Renal Transplant Recipients

Abstract: Sirolimus and cyclosporine (CsA) prevent acute rejection in man when used as primary therapies in triple drug regimens. Sirolimus does not act via the calcineurin pathway and therefore is not expected to produce the same renal side-effects. This paper presents the pooled 2-year data analysis of renal function parameters from two open-label, randomized, multicenter studies. Patients (18-68 years) receiving a primary renal allograft were randomized to receive concentration-controlled sirolimus (n Ω 81) or CsA (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(102 citation statements)
references
References 27 publications
4
97
0
1
Order By: Relevance
“…This effect was surprising since lack of nephrotoxicity is a well-known characteristic of sirolimus (21)(22)(23)(24). Sirolimus exerts its immunosuppressive effect by inhibiting the mammalian target of rapamycin, an enzyme required for T-and B-cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was surprising since lack of nephrotoxicity is a well-known characteristic of sirolimus (21)(22)(23)(24). Sirolimus exerts its immunosuppressive effect by inhibiting the mammalian target of rapamycin, an enzyme required for T-and B-cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The target levels of sirolimus that were used in this study were based on early studies of CNI-free protocols in adults (44). Earlier, uncontrolled use of sirolimus in children suggested that they may have an increased rate of metabolism of the drug, requiring more frequent dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Because withdrawal or avoidance of calcineurin inhibitors has been associated with an 8 to 29% increase in GFR, calcineurin-free regimens have the promise of significantly improving graft survival (11)(12)(13)(14)(15)(16). So far in early trials with early withdrawal or complete avoidance of calcineurin inhibitors, AR rates similar to those seen with calcineurin inhibitors have been achieved (13)(14)(15)(16). However, if AR rates are significantly higher with calcineurin-free regimens, then the detrimental effect of AR could negate the benefit of reduced renal toxicity with this approach to immunosuppression.…”
Section: Discussionmentioning
confidence: 99%